Protectionism, bilateral integration, and the cross section of exchange rate returns in US presidential debates - Jantke de Boer; Stefan Eichler; Ingmar Rövekamp (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2022)
We study the impact of US presidential election TV debates on intraday exchange rates of 96 currencies from 1996 to 2016. Expectations about protectionist measures are the main transmission channel of debate outcomes. Currencies of countries with high levels of bilateral foreign trade with the US depreciate if the election probability of the protectionist candidate increases during the debate. We rationalize our results in a model where a debate victory of a protectionist candidate raises expectations about future tariffs and reduces future net exports to the US, resulting in relative depreciation of currencies with high bilateral trade integration.
urn:nbn:de:bsz:14-qucosa2-818938
Keywords: F31; G15; G14; D72; 330; Exchange Rates; US Presidential Elections; TV Debates; Protectionism; Bilateral Trade Integration